P PENGARUH KOMPRES HANGAT TERHADAP PENGURANGAN INTENSITAS NYERI KALA I FASE AKTIF AKSELERASI DI BPM KURNIA DELI TUA KECAMATAN DELI TUA KABUPATEN DELI SERDANG TAHUN 2022 - Rasyid Sulaiman; Mutiara Dwi Yanti; Stefani Anastasia Sitepu; Suryani Mitra Damanik (JURNAL ILMIAH DHDT - KEBIDANAN, 2022)
Abstract Labor is the process of expelling a fetus that is born naturally in full pregnancy (32-42 weeks) with a posterior head presentation within 18 hours without complications for both mother and fetus. Some mothers feel traumatized to give birth again for fear of experiencing pain during childbirth. For mothers who have given birth, pain often occurs during childbirth, but if it is not handled properly it can cause other problems. One alternative that is done to reduce labor pain is to use a warm compress. The purpose of this study was to determine the effect of warm water compresses on reducing the intensity of labor pain during the active phase of acceleration at BPM Kurnia, Deli Tua District, Deli Serdang Regency in 2022. The research method used was Pre-experimental Design with a one group pretest-posttest design. The population in this study were all pregnant women in the first stage of the active phase, with a population of 25 respondents. The sampling technique in this study used a purposive sampling technique, with a sample of 20 respondents. The results showed a reduction in the intensity of labor pain before and after being given a warm compress, namely 3.750 gr/dl with a standard deviation of 1.916, the mean standard error of 0.428. And 95% Cl = 2.853-2.647 with a p value of 0.000. Research conclusions Based on the data above, it is known that the results of the Paired T-Test test obtained a p-value of which means <0.005. Thus, it can be concluded that there is an average effect of reducing the intensity of labor pain before (pretest) and after (posttest) given the intervention, so it can be said there is the effect of warm compresses on reducing the intensity of labor pain in the first stage of the active phase of acceleration at BPM Kurnia in 2022.